Assessment of the Performance of Magnetic Resonance Imaging/Ultrasound Fusion Guided Prostate Biopsy against a Combined Targeted Plus Systematic Biopsy Approach Using 24-Core Transperineal Template Saturation Mapping Prostate Biopsy - Francis Ting; Pim J. Van Leeuwen; James Thompson; Ron Shnier; Daniel Moses; Warick Delprado; Phillip D. Stricker (Prostate Cancer)
Objective. To compare the performance of multiparametric resonance imaging/ultrasound fusion targeted biopsy (MRI/US-TBx) to a combined biopsy strategy (MRI/US-TBx plus 24-core transperineal template saturation mapping biopsy (TTMB)). Methods. Between May 2012 and October 2015, all patients undergoing MRI/US-TBx at our institution were included for analysis. Patients underwent MRI/US-TBx of suspicious lesions detected on multiparametric MRI +/- simultaneous TTMB. Subgroup analysis was performed on patients undergoing simultaneous MRI/US-TBx + TTMB. Primary outcome was PCa detection. Significant PCa was defined as ≥Gleason score (GS) 3+4=7 PCa. McNemar’s test was used to compare detection rates between MRI/US-TBx and the combined biopsy strategy. Results. 148 patients underwent MRI/US-TBx and 80 patients underwent MRI/US-TBx + TTMB. In the MRI/US-TBx versus combined biopsy strategy subgroup analysis (n=80), there were 55 PCa and 38 significant PCa. The detection rate for the combined biopsy strategy versus MRI/US-TBx for significant PCa was 49% versus 40% (p=0.02) and for insignificant PCa was 20% versus 10% (p=0.04), respectively. Eleven cases (14%) of significant PCa were detected exclusively on MRI/US-TBx and 7 cases (8.7%) of significant PCa were detected exclusively on TTMB. Conclusions. A combined biopsy approach (MRI/US-TBx + TTMB) detects more significant PCa than MRI/US-TBx alone; however, it will double the detection rate of insignificant PCa.